2018
DOI: 10.1557/mrc.2017.130
|View full text |Cite
|
Sign up to set email alerts
|

Metal organic framework-modified nitrogen-doped graphene oxygen reduction reaction catalyst synthesized by nanoscale high-energy wet ball-milling structural and electrochemical characterization

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The precursor material was ground for 16 h, and the grinding speed was controlled and varied, because the high energy from the ball mill can impact the physical and chemical properties of the ZIF-8 particles. It was observed that at 350 RPM the catalyst showed the optimum current density, which was even higher than current density of 10 wt % Pt/C [22]. This increase in the electrochemical performance of the catalyst was attributed to the micro porosity induced by the ZIF-8 structure and the chemical interactions of N-G and ZIF-8 particles, which increased the pyridinic active sites on the imidazolate framework and also enhanced the surface density of the active sites for improved ORR [22][23][24].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The precursor material was ground for 16 h, and the grinding speed was controlled and varied, because the high energy from the ball mill can impact the physical and chemical properties of the ZIF-8 particles. It was observed that at 350 RPM the catalyst showed the optimum current density, which was even higher than current density of 10 wt % Pt/C [22]. This increase in the electrochemical performance of the catalyst was attributed to the micro porosity induced by the ZIF-8 structure and the chemical interactions of N-G and ZIF-8 particles, which increased the pyridinic active sites on the imidazolate framework and also enhanced the surface density of the active sites for improved ORR [22][23][24].…”
Section: Resultsmentioning
confidence: 93%
“…It can be seen from Figure 2e,f that the N-G/MOF catalyst had both amorphous and crystalline structures inherited from N-G and MOF structures, with an average particle size of 955 nm. From our previous study, it was proven that nitrogen-doping and particle size can be controlled by the grinding speed and grinding time of ball milling [20][21][22].…”
Section: Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The serum is the fluid that remains after removing fibrinogen, also referred to as clotting agents. The serum is harder to obtain because it needs additional separation [64][65][66][67]. Sample extraction is not limited to the options mentioned above.…”
Section: Specimen and Sample Typesmentioning
confidence: 99%
“…Therefore, efforts have been made to develop Pt alternative catalysts for ORR. In alkaline media, electrocatalysts with various categories have been developed, further, the corresponding mechanisms have been explored, including nonmetal-doped carbon materials [4][5][6][7][8], carbon-transition metal hybrids [9][10][11][12][13][14][15][16][17][18][19][20], metal organic framework-modified nitrogen-doped graphene [21][22][23], and transition metal oxides [24][25][26][27][28]. Nonmetal heteroatom doped carbon materials and transition metal oxides have especially been given attention due to their advantages of high electron conductivity and favorable redox reversibility, respectively [29,30].…”
Section: Introductionmentioning
confidence: 99%